PRODUCT QUALITY OF MUNICIPAL SOLID WASTE COMPOST FROM PILOT AND REAL SCALE PLANTS - Varank, Gamze; Demir, Ahmet; Akkaya, Ebru; Bilgili, M. Sinan; Ozkaya, Bestamin (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2009)
In this study; properties and quality of municipal solid waste compost were investigated and compared in pilot-and real-scale plants. The compost quality was determined in terms of pH, moisture content, organic matter content, total Kjeldahl nitrogen (TKN), total phosphorus (TP), total organic carbon (TOC), C/N ratio, phytotoxicity, Salmonella sp., stability index (SI), heavy metal and evaluated considering German compost quality standard (LAGA). Further, the applicability and utility of the end products from two aerobic pilot scale landfill reactors with (A1) and without (A2) leachate recirculation and Istanbul Solid Waste Recycling and Composting Plant (CP) were evaluated. pH and organic content of compost products were around 7.7-8.0 and 36.5-46.5%, respectively. The compost moisture content in A1 reactor was determined as 70%, which was the highest value due to the leachate recirculation. Carbon to nitrogen (C/N) ratios were 7.3, 5.3 and 12.8 in A1, A2 and CP end-products in respective order. Heavy metal concentrations of Cu, Cd and Cr exceeded the allowable standards values stipulated for compost products. Salmonella sp. as a hygienic indicator did not found in the compost products. All the end products were in the non-toxic class of the relevant standards as per phytotoxicity tests carried out on compost and soil mixtures of 25 and 50%, and these products were mature and stabile.
Keywords: Municipal solid waste; aerobic landfilling; composting; product quality; LEACHATE RECIRCULATION; LANDFILLS; MATURITY; Environmental Sciences & Ecology